A method for preparing low bulk density copper powder and copper powder

By adding urea and glycine to the electrolyte as a combined additive and electrolyzed under specific electrolytic conditions, the existing copper powder has been solved, and copper powder with low loose density and developed foliar branches has been successfully prepared to meet the use needs of high-end materials.

CN116479476BActive Publication Date: 2025-04-29CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310420479.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-04-29
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The copper powder prepared by existing electrolytic methods has high loose density and is difficult to meet the needs of high-end materials.

Method used

Copper sulfate, sulfuric acid, urea, glycine and water are prepared to form an electrolyte, and electrolyze under specific conditions. The precipitated products from the cathode are collected for deionization, saponification coating, dehydration and vacuum drying to prepare low-loose density copper powder.

Benefits of technology

Copper powder with well-developed fern leaves is prepared stably, with a loose density of less than 0.4 g/cm3 and a purity of 99.99%, which is suitable for the production of high-end materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116479476B_ABST
    Figure CN116479476B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing copper powder with low apparent density and the copper powder. The preparation method is as follows: copper sulfate, sulfuric acid, urea, glycine and water are formulated to form electrolyte W; the electrolyte is placed in an electrolytic cell for electrolysis; after electrolysis, the product deposited on the cathode is collected, rinsed 4 - 5 times with deionized water saturated with nitrogen in a nitrogen glove box, then saponified and coated, rinsed with deionized water saturated with nitrogen, dehydrated and vacuum dried to obtain the copper powder with low apparent density. The copper powder has a fern-like dendritic structure, the crystal arms and edges of the primary dendrites and secondary dendrites are well developed, the apparent density value is less than 0.4 g / cm<supgt;3< / supgt;, and the purity is ≥99.99%. The method provided by the present invention has simple steps, the prepared copper powder has small particle size and low apparent density, and can meet the use requirements of high-end materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation, and in particular to a method for preparing low bulk density copper powder and the copper powder. Background Art

[0002] Copper powder is an important basic material in the nonferrous metallurgical industry. It can be alloyed with other metals or non-metals to form materials with good electrical and thermal conductivity, corrosion resistance and non-magnetic properties. It is widely used in friction materials, oil-containing bearings, brush products, electrical contact materials, conductive materials, diamond products, filters and mechanical parts. Copper powder with low bulk density and well-developed dendrites is widely used in aerospace, high-end CNC machine tools, robots, and national defense and military industries. It is an irreplaceable functional metal powder material for manufacturing metal brushes used in precision positioning motors. However, low bulk density copper powder suitable for the production of high-end metal brushes is currently only produced in small quantities by several companies in Japan, the United Kingdom, Germany, etc., and these companies keep the technology confidential and blockade. Due to the large gap between the quality of copper powder in my country and the demand for the development of high-end materials, it can only rely on high-priced imports to meet industrial needs.

[0003] Although there are many methods for producing copper powder, electrolysis is still the best way to industrially prepare low bulk density copper powder. The traditional electrolytic copper powder preparation method uses pure copper plate as a soluble anode and pure copper sheet as a cathode. Under certain process conditions, the copper on the anode is dissolved by applying direct current (Cu-2e→Cu 2+ ), copper powder is precipitated on the cathode (Cu 2+ +2e→Cu), and at the same time, hydrogen evolution reaction occurs on the cathode surface due to polarization effect. After a certain period of electrolysis, the copper powder deposited on the surface of the cathode plate is scraped off by artificial methods, and the copper powder obtained has a cauliflower-like or sorghum-like morphology, short dendrites, and agglomeration occurs when the copper powder is fine. Therefore, the crystal arms and edges of the copper powder dendrites produced by the method of changing the copper ion concentration, sulfuric acid concentration and electrolysis control parameters in the traditional electrolyte usually grow unevenly, and it is difficult to stably prepare low-loose density electrolytic copper powder with well-developed crystal arms and edges of primary and secondary dendrites and well-developed dendrites.

[0004] Under the existing production conditions, how to use electrolysis to prepare low bulk density less than 1.0g / cm 3 Copper powder with well-developed dendrites has become a difficult problem that the industry urgently needs to overcome. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to solve the problem that the copper powder prepared by the existing electrolytic method has a high loose density and is difficult to meet the use requirements of high-end materials, and to provide a method for preparing low loose density copper powder and copper powder. The method has simple steps and the prepared copper powder has a small particle size and low loose density, which can meet the use requirements of high-end materials.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for preparing low bulk density copper powder comprises the following steps:

[0008] Copper sulfate, sulfuric acid, urea, glycine and water are mixed to form an electrolyte W;

[0009] The electrolyte is placed in an electrolytic cell for electrolysis; wherein the cathode plate is made of stainless steel and the anode plate is made of copper; the distance between the anode and cathode is controlled to be 3 to 10 cm, and the electrolyte temperature is 50 to 60°C and the current density is 1600 to 1800 A / m 2 , the electrolysis time is 5 to 10 minutes;

[0010] After the electrolysis is completed, the product precipitated at the cathode is collected, rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water, dehydrated and vacuum dried to obtain low bulk density copper powder.

[0011] Preferably, in the electrolyte W, the concentration of divalent copper ions is 0.3-0.8 mol / L, the concentration of sulfuric acid is 1.5-2.1 mol / L, the amount of glycine added is 0.025-0.080 mol / L, the amount of urea added is 0.01-0.04 mol / L, and the resistivity value of deionized water is ≥18 MΩ·cm.

[0012] When preparing electrolyte W, when the concentration of the additive glycine is lower than 0.025 mol / L and the concentration of urea is lower than 0.01 mol / L, the fern-like dendrites of the electrolytic copper powder cannot be fully unfolded, resulting in an increase in the bulk density and particle size of the copper powder, and an uneven distribution of the particle size of the copper powder. When the concentration of the additive glycine exceeds 0.08 mol / L and the concentration of urea exceeds 0.04 mol / L, the morphology of the electrolytic copper powder changes from a developed fern-like shape to small and broken irregular crystals. Therefore, a reasonable additive concentration is more conducive to obtaining a developed fern-like copper powder, and too low or too high an additive concentration will result in the failure to obtain a copper powder with a developed fern-like dendrite structure.

[0013] Preferably, the molar ratio of urea to glycine is 1:(3-2), preferably 1:2.

[0014] Furthermore, the preparation method of the electrolyte W is:

[0015] Dissolve copper sulfate and sulfuric acid in deionized water, heat to 80-90°C, and add glycine under stirring at 400-600 r / min;

[0016] After 1 to 3 hours, stirring is stopped. After the solution temperature drops to 40 to 50°C, urea is added while stirring at 400 to 600 r / min to obtain electrolyte W.

[0017] The prepared electrolyte W needs to be sealed and stored in a constant temperature environment of 50-60°C, and the shelf life is 24 hours. Of course, the electrolyte W is better when it is prepared and used immediately.

[0018] Preferably, copper sulfate and sulfuric acid are dissolved in deionized water in sequence, the solution is heated to 85° C., and glycine is added under stirring at 500 r / min;

[0019] After 2 h, stirring was stopped, and after the solution temperature dropped to 50°C, urea was added under stirring at 500 r / min to obtain electrolyte W.

[0020] Preferably, the anode plate is made of 99.99% copper, and the cathode plate is made of 316L or 904L stainless steel plate.

[0021] Preferably, the anode plate and cathode plate are polished with 400 mesh, 800 mesh, 1500 mesh, 3000 mesh and 5000 mesh sandpaper respectively before electrolysis, ultrasonicated in anhydrous ethanol for 1 hour, ultrasonicated in 5% HCl for 5 minutes, and then cleaned with deionized water for use.

[0022] As a preferred method, when the electrolyte is placed in the electrolytic cell for electrolysis, the distance between the cathode and cathode is controlled to be 5 to 8 cm, and the electrolyte temperature is 60°C and the current density is 1600 A / m 2 Electrolyze for 10 min.

[0023] The present invention also provides a copper powder prepared by the method for preparing a copper powder with low bulk density; the copper powder has a fern-like dendrite structure, well-developed branches, uniform size distribution, well-developed crystal arms and edges of primary and secondary dendrites, and a bulk density value of less than 0.4 g / cm 3 , purity ≥99.99%.

[0024] Furthermore, the fern-like dendrites of the copper powder have a trunk length of 3.5 to 9.5 μm, a branch length of 0 to 4.5 μm, and a median particle size range of 5 to 9 μm.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. The preparation method provided by the present invention adds urea and glycine as combined additives in the electrolyte. Both substances are soluble green substances, non-toxic and pollution-free, and the raw materials are cheap. There is no residue after cleaning, and no new impurities are introduced. During electrolysis, urea and glycine will form complex ions with divalent copper ions respectively, play the role of structural directing agents in the nucleation and growth process of cathode copper crystals, and make the crystal plane of copper deposition preferentially oriented. At the same time, the combined additive can also increase the cathode electrochemical polarization and optimize the peak current density and peak potential of the copper deposition reaction. These effects play a vital role in the formation of fern-like well-developed dendrites during the electrodeposition process, so that copper powder with well-developed fern-like branches can be stably prepared. The method can prepare copper powder with a purity of more than 99.99%, and the steps are simple, easy to operate, highly safe, and suitable for industrial production.

[0027] 2. The copper powder provided by the present invention has a fern-like dendrite structure, with well-developed branches and uniform size distribution. The crystal arms and edges of the primary dendrites (branches) and secondary dendrites (branches and leaves) are well developed. The length of the fern-like dendrites is 3.5 to 9.5 μm, the length of the branches is 0 to 4.5 μm, the median particle size ranges from 5 to 9 μm, and the bulk density is less than 0.4 g / cm 3 The fern-like morphology is significantly different from the sorghum-spiked electrolytic copper powder without additives, and is particularly useful for manufacturing metal brush products used in precise positioning of electric motors. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the copper powder prepared in Example 1 of the present invention.

[0029] Figure 2 This is a SEM image of the copper powder prepared in Example 2 of the present invention.

[0030] Figure 3 This is a SEM image of the copper powder prepared in Example 3 of the present invention.

[0031] Figure 4 This is the SEM image of the copper powder prepared in Comparative Example 1.

[0032] Figure 5 This is the SEM image of the copper powder prepared in Comparative Example 2.

[0033] Figure 6 This is the SEM image of the copper powder prepared in Comparative Example 3. DETAILED DESCRIPTION

[0034] The embodiment of the present invention provides a method for preparing low bulk density copper powder, comprising the following steps:

[0035] Copper sulfate, sulfuric acid, urea, glycine and water are mixed to form an electrolyte W;

[0036] The electrolyte is placed in an electrolytic cell for electrolysis; wherein the cathode plate is made of 316L or 904L stainless steel, and the anode plate is made of 99.99% copper; the distance between the cathode and cathode is controlled to be 3 to 10 cm, and the electrolyte temperature is 50 to 60°C and the current density is 1600 to 1800 A / m 2 , the electrolysis time is 5 to 10 minutes;

[0037] After the electrolysis is completed, the product precipitated at the cathode is collected, rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water, dehydrated and vacuum dried to obtain low bulk density copper powder.

[0038] Example 1

[0039] 0.4 mol / L copper sulfate and 1.6 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and the solution was heated to 85°C. 0.05 mol / L glycine was added under stirring at 500 r / min, and stirring was stopped after 2 h. After the solution temperature dropped to 50°C, 0.025 mol / L urea was added under stirring at 500 r / min to obtain electrolyte W.

[0040] The electrolyte W was transferred to a copper electrolytic cell, and a cathode plate made of 316L stainless steel and an anode plate made of 99.99% copper were placed. The electrolyte temperature was 60.3°C, the distance between the anode and the cathode was 6.5 cm, and the cathode current density was 1600 A / m 2 Electrolyze for 10 min.

[0041] Among them, the area of ​​the stainless steel cathode plate is 0.1m 2 , thickness is 2mm, the area of ​​copper anode plate is 0.1m 2 , thickness is 10mm. Before electrolysis, the cathode plate and the anode plate were polished with 400 mesh, 800 mesh, 1500 mesh, 3000 mesh and 5000 mesh sandpaper respectively, ultrasonicated in anhydrous ethanol for 1h, and then ultrasonicated in 5% HCl for 5min, and then cleaned with deionized water for use (the same below).

[0042] After the electrolysis is completed, the product precipitated at the cathode is collected, and the obtained product is rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried to obtain low bulk density copper powder.

[0043] The SEM image of the copper powder prepared in this embodiment is as follows Figure 1 As shown. Figure 1It can be seen that the crystal arms and edges of the primary and secondary dendrites of the copper powder are well developed, the fern-like branches are well developed, and the size distribution is uniform. The length of the fern-like dendrites is in the range of 3.5 to 6.8 μm, the length of the branches is in the range of 0 to 2 μm, and the median particle size of the copper powder is 5.26 μm. The bulk density of the copper powder was measured by a Hall flow meter bulk density meter (the same below), which is 0.37 g / cm 3 , using ICP detection (the same below) the copper powder purity is ≥99.99%.

[0044] Example 2

[0045] 0.5 mol / L copper sulfate and 1.5 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and the solution was heated to 85°C. 0.04 mol / L glycine was added under stirring at 500 r / min, and stirring was stopped after 2 h. After the solution temperature dropped to 50°C, 0.02 mol / L urea was added under stirring at 500 r / min to obtain electrolyte W.

[0046] The electrolyte W was transferred to a copper electrolytic cell, and a cathode plate made of 904L stainless steel and an anode plate made of 99.99% copper were placed. The electrolyte temperature was 60.0°C, the distance between the anode and the cathode was 7.0 cm, and the cathode current density was 1600 A / m 2 Electrolyze for 10 min.

[0047] After the electrolysis is completed, the product precipitated at the cathode is collected, and the obtained product is rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried to obtain low bulk density copper powder.

[0048] The SEM image of the copper powder prepared in this embodiment is as follows Figure 2 As shown. Figure 2 It can be seen that the crystal arms and edges of the primary and secondary dendrites of the copper powder are well developed, the fern-like branches are well developed, and the size distribution is uniform. The length of the fern-like dendrites is in the range of 4.04 to 8.86 μm, the length of the branches is in the range of 0 to 4.4 μm, and the median particle size of the copper powder is 6.73 μm. The bulk density of the copper powder measured by the funnel method is 0.33 g / cm 3 , ICP was used to detect the purity of copper powder ≥99.99%.

[0049] Example 3

[0050] 0.3 mol / L copper sulfate and 1.5 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and the solution was heated to 85°C. 0.03 mol / L glycine was added under stirring at 500 r / min, and stirring was stopped after 2 h. After the solution temperature dropped to 50°C, 0.015 mol / L urea was added under stirring at 500 r / min to obtain electrolyte W.

[0051] The electrolyte W was transferred to a copper electrolytic cell, and a cathode plate made of 316L stainless steel and an anode plate made of 99.99% copper were placed. The electrolyte temperature was 60.1°C, the distance between the anode and the cathode was 6.5 cm, and the cathode current density was 1700 A / m 2 Electrolyze for 10 min.

[0052] After the electrolysis is completed, the product precipitated at the cathode is collected, and the obtained product is rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried to obtain low bulk density copper powder.

[0053] The SEM image of the copper powder prepared in this embodiment is as follows Figure 3 As shown. Figure 3 It can be seen that the crystal arms and edges of the primary and secondary dendrites of the copper powder are well developed, the fern-like branches are well developed, and the size distribution is uniform. The length of the fern-like dendrites is in the range of 3.87-8.73 μm, the length of the branches is in the range of 0-4.3 μm, and the median particle size of the copper powder is 5.56 μm. The bulk density of the copper powder measured by the funnel method is 0.34 g / cm 3 , ICP was used to detect the purity of copper powder ≥99.99%.

[0054] Comparative Example 1

[0055] 0.4 mol / L copper sulfate and 1.6 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and transferred to a conventional copper electrolytic cell, and anode and cathode plates were placed (the cathode and cathode plates were the same as in Example 1, the same below), the electrolyte temperature was 60.2°C, the distance between the anode and the cathode was 6.5 cm, and the cathode current density was controlled to be 1600 A / m 2 Electrolyze for 10 min.

[0056] After the electrolysis is completed, the cathode product is collected, and the obtained product is rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried to obtain electrolytic copper powder, which is then vacuum-sealed and stored.

[0057] Figure 4The figure is a schematic diagram of the copper powder morphology obtained in comparative example 1. After measurement, the copper powder obtained is in the shape of sorghum spikes, with short dendrites, and agglomeration occurs when the copper powder is fine. The average particle size of the prepared copper powder is 22.35 μm, and the bulk density is 1.22 g / cm 3 , copper powder purity ≥99.99%.

[0058] Comparative Example 2

[0059] 0.4 mol / L copper sulfate and 1.6 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and the solution was heated to 85°C. 0.01 mol / L glycine was added under stirring at 500 r / min. After 2 h, stirring was stopped and the solution temperature was waited to drop to 50°C. Then, 0.005 mol / L urea was added under stirring at 500 r / min to obtain electrolyte W.

[0060] The electrolyte W was transferred to a conventional copper electrolytic cell, and the anode and cathode plates were placed. The electrolyte temperature was 60.1°C, the distance between the anode and cathode was 6.5 cm, and the cathode current density was controlled to be 1600 A / m 2 After the electrolysis, in a nitrogen glove box, the copper powder was washed with nitrogen-saturated deionized water for 4 to 5 times, then saponified and coated, washed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried, and finally the copper powder was vacuum sealed and stored to obtain the copper powder.

[0061] Figure 5 The figure is a schematic diagram of the copper powder morphology obtained in comparative example 2. After measurement, the crystal arms and edges of the primary and secondary dendrites of the copper powder were not fully developed, the fern-like branches were not well developed, and the size distribution was uneven. The length of the dendrite trunk ranged from 4.55 to 15.86 μm, the length of the branches ranged from 0 to 3 μm, the median particle size of the copper powder was 9.46 μm, and the bulk density was 0.48 g / cm 3 , copper powder purity ≥99.99%.

[0062] Comparative Example 3

[0063] 0.4 mol / L copper sulfate and 1.6 mol / L sulfuric acid were dissolved in 18.25 MΩ·cm deionized water, and the solution was heated to 85°C. 0.2 mol / L glycine was added under stirring at 500 r / min. After 2 h, stirring was stopped and the solution temperature was waited to drop to 50°C. Then, 0.1 mol / L urea was added under stirring at 500 r / min to obtain electrolyte W.

[0064] The electrolyte W was transferred to a conventional copper electrolytic cell, and the anode and cathode plates were placed. The electrolyte temperature was 60.2°C, the distance between the anode and cathode was 6.5 cm, and the cathode current density was controlled to be 1600 A / m 2After the electrolysis, in a nitrogen glove box, the copper powder was washed with nitrogen-saturated deionized water for 4 to 5 times, then saponified and coated, washed with nitrogen-saturated deionized water twice, dehydrated and vacuum dried, and finally the copper powder was vacuum sealed and stored to obtain the copper powder.

[0065] Figure 6 The figure is a schematic diagram of the copper powder morphology obtained in comparative example 3. As can be seen from the figure, the copper powder obtained has severe dendrite fragmentation and no obvious dendrites. The median particle size of the copper powder is 5.18 μm, and the bulk density is 0.78 g / cm 3 , copper powder purity ≥99.99%.

[0066] The components and proportions of the electrolytes used in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0067] Table 1

[0068]

[0069] From Examples 1 to 3, it can be seen that the copper powder prepared by the method provided by the present invention has well-developed fern-like dendrites, the crystal arms and edges of the primary and secondary dendrites are well-developed, the fern-like branches are well-developed, and the size distribution is uniform. The length of the trunk of the fern-like dendrites ranges from 3.5 to 9.5 μm, the length of the branches ranges from 0 to 4.5 μm, and it has a well-developed dendrite structure, and its loose density is less than 0.4 g / cm 3 In Comparative Example 1, glycine and urea were not added as additives, so the copper powder prepared therefrom was in the shape of sorghum spikes, with short dendrites, and agglomeration occurred when the copper powder was fine. The average particle size of the copper powder was 22.35 μm, and the bulk density was 1.22 g / cm 3 . In Comparative Examples 2 and 3, although glycine and urea were added as additives, in Comparative Example 2, the concentration of glycine was lower than 0.025 mol / L and the concentration of urea was lower than 0.01 mol / L, and the fern-like dendrites of the prepared copper powder could not be fully unfolded, resulting in the increase of the bulk density and particle size of the copper powder, and the uneven distribution of the particle size of the copper powder, which was manifested as an increase in the bulk density compared with the embodiment. In Comparative Example 3, the concentration of the additive glycine exceeded 0.08 mol / L and the concentration of urea exceeded 0.04 mol / L, and the morphology of the prepared copper powder changed from a developed fern-like shape to small and broken irregular crystals, and the bulk density of the copper powder was significantly increased compared with the embodiment.

[0070] It can be seen that the copper powder prepared by the preparation method provided by the present invention has a fern-like dendrite structure, with well-developed branches, uniform size distribution, and well-developed crystal arms and edges of primary dendrites (branches) and secondary dendrites (branches and leaves). The length of the fern-like dendrites is 3.5 to 9.5 μm, the length of the branches is 0 to 4.5 μm, the median particle size range is 5 to 9 μm, and the bulk density is less than 0.4 g / cm3 The fern-like morphology is significantly different from the sorghum-spiked electrolytic copper powder without additives, and is particularly useful for manufacturing metal brush products used in precise positioning of electric motors.

[0071] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing low bulk density copper powder, characterized in that: The following steps are included: Copper sulfate, sulfuric acid, urea, glycine and water are mixed to form an electrolyte W; in the electrolyte W, the concentration of divalent copper ions is 0.3-0.8 mol / L, the concentration of sulfuric acid is 1.5-2.1 mol / L, the amount of glycine added is 0.025-0.080 mol / L, the amount of urea added is 0.01-0.04 mol / L, and the resistivity value of deionized water is ≥18 MΩ·cm; the molar ratio of urea to glycine is 1:(3-2); The electrolyte is placed in an electrolytic cell for electrolysis; wherein the cathode plate is made of stainless steel and the anode plate is made of copper; the distance between the anode and cathode is controlled to be 3 to 10 cm, and the electrolyte temperature is 50 to 60°C and the current density is 1600 to 1800 A / m 2 , the electrolysis time is 5 to 10 minutes; After the electrolysis is completed, the product precipitated at the cathode is collected, rinsed with nitrogen-saturated deionized water for 4 to 5 times in a nitrogen glove box, then saponified and coated, rinsed with nitrogen-saturated deionized water, dehydrated and vacuum dried to obtain low bulk density copper powder.

2. The method for preparing low bulk density copper powder according to claim 1, characterized in that: The preparation method of the electrolyte W is: Dissolve copper sulfate and sulfuric acid in deionized water, heat to 80-90°C, and add glycine under stirring at 400-600 r / min; After 1 to 3 hours, stirring is stopped. After the solution temperature drops to 40 to 50°C, urea is added while stirring at 400 to 600 r / min to obtain electrolyte W.

3. The method for preparing low bulk density copper powder according to claim 2, characterized in that: Dissolve copper sulfate and sulfuric acid in deionized water, heat the solution to 85°C, and add glycine under stirring at 500 r / min; After 2 h, stirring was stopped, and after the solution temperature dropped to 50°C, urea was added under stirring at 500 r / min to obtain electrolyte W.

4. The method for preparing low bulk density copper powder according to claim 1, characterized in that: The anode plate is made of 99.99% red copper, and the cathode plate is made of 316L or 904L stainless steel plate.

5. The method for preparing low bulk density copper powder according to claim 4, characterized in that: Before electrolysis, the anode plate and cathode plate were polished with 400 mesh, 800 mesh, 1500 mesh, 3000 mesh and 5000 mesh sandpaper respectively, ultrasonicated in anhydrous ethanol for 1 hour, ultrasonicated in 5% HCl for 5 minutes, and then cleaned with deionized water for use.

6. The method for preparing low bulk density copper powder according to claim 1, characterized in that: When the electrolyte is placed in the electrolytic cell for electrolysis, the distance between the cathode and cathode is controlled to be 5-8 cm, and the electrolyte temperature is 60°C and the current density is 1600A / m 2 Electrolyze for 10 min.

Citation Information

Patent Citations

  • Method of producing copper powder

    JP2019210508A

  • Copper powder producing electrolyte

    RU2254209C1